Negotiation of Aesthetic Habits, Cultural Symbols, and Identity of Lampung Culture - Habsary, Dwiyana; Tejo Sampurno, Muchammad Bayu (Aisthesis, 2024)
This study profoundly analyzes the balance between traditionalism and modernization within the Lampung culture. In most aspects, it dwells on the traditional value system of Pi’il, the philosophical symbolism of traditional dressing in cultures, and the cultural implications, which are synonymous with dance and ornamental art. Lampung’s culture and identity as aesthetic habits are explicitly found in Pi’il as a source of dignity and harmony of the social body amidst contemporary globalization forces. Instead, Pi’il’s adaptation to the present life forms seems to be characterized by young generations. The study also involves the deep-seated philosophical connotations hidden beneath forms or defined in chosen color and shape, and this form is another influence of Indonesian traditional culture; the Siger crown and Ruwi bracelet, which to Lampung’s natives are more than mere aesthetic elements but signs of socio-cultural beliefs; and dance as aesthetic habits from its cultural values and precisely how the Sigeh Penguten traditional dance functions as such is researched. Dance like Jong Simpuh and Ngrujung, containing unique poses, represents three crucial cultural practices and values such as hospitality rights, social hierarchy, and ubiquitous relationships. Then, the significant patterns of visual art forms in the culture Lampung, “Pucuk Rebung” and “jung”, are used as symbols of identity in public places. These motifs and the regional script “Aksara Ka Ga Nga” are vital because they ensure a culture or identity awareness even in an era where modernization efforts threaten to oust older influences.